Mid-upper Arm Circumference as an Indicator of Quality of Life of Patients with Advanced Cancer. Issue 1 (January 2023) - Won, Seon-Hye; Hiratsuka, Yusuke; Suh, Sang-Yeon; Bae, Hayoung; Choi, Sung-Eun; Kim, Yu Jung; Kang, Beodeul; Lee, Si Won; Suh, Koung Jin; Kim, Ji-Won; Kim, Se Hyun; Kim, Jin Won; et al.
Objective: Mid-upper arm circumference (MUAC) has been used to assess malnutrition and health status across various disease groups. However, it is unclear whether MUAC is associated with quality of life (QOL) of patients with advanced cancer. Our goal was to investigate the relationship between MUAC and QOL in ambulatory out-patients with advanced cancer.Method: This was a cross-sectional study conducted in a tertiary cancer center in South Korea. A total of 200 patients with advanced cancer at oncology clinics of Seoul National University Bundang Hospital from March 2016 to January 2019 were enrolled. Out-patients with advanced cancer whose survival was expected to be less than one year by their oncologists were enrolled. QOL of patients was evaluated using the European Organization for Research and Treatment of Cancer quality of life questionnaire core 30 (EORTC QLQ-C30). Associations of QOL with MUAC and nutritional parameters were examined with generalized linear models.Results: The most common cancer sites were the lung, colon or rectum, and genitourinary tract. In univariate analyses, significant factors associated with higher summary score of EORTC QLQ-C30 were higher MUAC (≥ 26.5 cm, p < 0.001), higher body mass index (BMI) (≥ 22 kg/m 2, p < 0.001), higher serum albumin (≥ 3.7 g/dL, p < 0.01), higher creatinine (≥ 0.8 mg/dL, p = 0.023), and higher uric acid (≥ 5 mg/dL, p < 0.01). In multivariate analysis, higher serum albumin (≥ 3.7 g/dL, p < 0.01) and higher MUAC (≥ 26.5 cm, p = 0.03) were independently associated with better summary score of EORTC QLQ-C-30.Conclusion: MUAC was highly associated with QOL in terms of summary score and overall health status. Thus, MUAC, with its simplicity, can be a useful tool to reflect QOL in patients with advanced cancer.